Use of neural network for optimization of energy cost in moving limb - Manavy, Yadulla; Zamanian-Azodi, Mona; Gilanchi, Samira; Omidi, Roghieh (Archives of Advances in Biosciences, 2014)
Artificial neural networks are used in many smart apparatus and different fields such as signal processing pattern diagnoses, military systems, medicine, financial systems, and artificial intelligence. In this article using quality of neural networks in optimizing energy cost in moving limb and its effectiveness in organization a cognitive function founded by presenting an algorithm for use in human smart robotics and worldwide research will be described and discussed. Neural system contributes to minimal cost energy in decision-making and command exportation to skeletal muscle and suggested optimal energy cost in skeletal muscle that could be presented in software conformation.